Award Prize "Dušan Bandić" for 2015 to Ivan Kovačević - Editorial Board (University of Belgrade, 2016)
Award Prize "Dušan Bandić" for 2015 to prof. Ivan Kovačević for the book "History of Serbian Anthropology", Belgrade, Dosije studio.